Back contact effect on electrodeposited CZTS kesterite thin films experimental and numerical investigation. (December 2019) - Toura, Hanae; Khattak, Yousaf Hameed; Baig, Faisal; Soucase, Bernabe Mari; Touhami, Mohamed Ebn
Graphical abstract: Highlights: Single step ED technique was used to fabricate CZTS kesterite thin films. Growth of CZTS on different substrates such as Mo, FTO, and ITO were investigated. Virtuous crystallinity on Mo substrates and phase purity was found around 450 °C. The band gaps of the annealed samples are found around 1.47 eV. Device performance was investigated for different substrates in SCAPS-1D. Abstract: Kesterite C u 2 Z n S n S 4 ( C Z T S ) with an optimal band gap of 1.5 e V is an auspicious material to be used as absorber layer high efficiency thin film photovoltaic cells. Effect of substrates on the morphology and structural properties of CZTS kesterite thin films were analyzed by depositing CZTS on Molybdenum, Indium doped tin oxide, and Fluorine doped tin oxide via electrochemical deposition method. The electrolyte contains C u S o 4, Z n S o 4, S n S o 4 and N a 2 S 2 O 3 as precursors, with N a 3 C 6 H 5 O 7 and C 4 H 6 O 6 as complexing agents. Electrochemical depositions were carried out at room temperature with a voltage of −1.05 V vs. Ag/AgCl reference electrode. Films were annealed at a temperature around 450 °C and then characterized by X-ray diffraction. The characterization shows the development of CZTS kesterite structure, with a good crystallinity on Mo substrates and phase purity, which were also confirmed by Raman spectroscopy and scanning electron microscopy. Then optical measurements showed that the deposited thin films present a bandgap of around 1.47 eV. Correspondingly, the effect of metal contact work function for these substrates were also investigated with the aid of device modeling software SCAPS. The analysis shows that for given solar cell structure, back contact/CZTS/CdS/ZnO, Mo substrates presented better performance.